2011
DOI: 10.1007/s10719-011-9358-x
|View full text |Cite
|
Sign up to set email alerts
|

Lumican is a major small leucine-rich proteoglycan (SLRP) in Atlantic cod (Gadus morhua L.) skeletal muscle

Abstract: Knowledge on fish matrix biology is important to ensure optimal fish -quality, -growth and -health in aquaculture. The aquaculture industry face major challenges related to matrix biology, such as inflammations and malformations. Atlantic cod skeletal muscle was investigated for collagen I, decorin, biglycan, and lumican expression and distribution by real-time PCR, immunohistochemical staining and Western blotting. Immunohistochemical staining and Western immunoblotting were also performed using antibodies ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…In mammals, SLRPs have been detected in osteoblast and hypertrophic chondrocytes of limb long bones and in developing bone matrices (Bianco et al 1990, Takagi et al 2000, Alini & Roughley 2001, Yang et al 2012 and appear to play a role related to establishing ossification fronts and matrix organization. All 3 proteins showed a molecular size between 40 and 50 kDa, which is in accordance with results from other teleosts (Tingbø et al 2012) and mammals (Iozzo 1999, Pedersen et al 2001) reflecting cross-species similarities. We found that SLRPs in Atlantic salmon osteoblasts are increasingly transcribed during differentiation in vitro, as described in mammalian osteoblast cell lines , Mochida et al 2003, Waddington et al 2003, Chen et al 2005, Parisuthiman et al 2005.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In mammals, SLRPs have been detected in osteoblast and hypertrophic chondrocytes of limb long bones and in developing bone matrices (Bianco et al 1990, Takagi et al 2000, Alini & Roughley 2001, Yang et al 2012 and appear to play a role related to establishing ossification fronts and matrix organization. All 3 proteins showed a molecular size between 40 and 50 kDa, which is in accordance with results from other teleosts (Tingbø et al 2012) and mammals (Iozzo 1999, Pedersen et al 2001) reflecting cross-species similarities. We found that SLRPs in Atlantic salmon osteoblasts are increasingly transcribed during differentiation in vitro, as described in mammalian osteoblast cell lines , Mochida et al 2003, Waddington et al 2003, Chen et al 2005, Parisuthiman et al 2005.…”
Section: Discussionsupporting
confidence: 88%
“…The nitrocellulose membrane was then probed with the polyclonal antibodies decorin (ab35378), lumican (ab70191) and biglycan (ab20033) (Abcam) diluted 1:5000 in Tris-buffered saline (TBS) added to 0.5% teleostan gelatine. These antibodies are specific to teleosts (Tingbø et al 2012). Alkaline phosphatise (AP) conjugated secondary antibodies (anti-mouse IgG(H+L), Promega) diluted 1:7500 were then applied to the membranes.…”
Section: Protein Extraction and Western Blotsmentioning
confidence: 99%
“…Previous studies using mouse models of LUM deficiency have determined its requirement for normal collagen fiber assembly in the skeletal muscle, [14] tendon [15] and cornea [16, 17]. We evaluated the spatiotemporal localization of LUM throughout cardiac development and using a LUM deficient mouse model determine a potentially critical role for LUM in murine cardiac development.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we immunolocalized lumican in the chordocytes of Atlantic salmon (Pedersen et al 2013 ). Lumican is reported to carry KS also in teleosts such as Atlantic cod (Tingbo et al 2012 ) and zebrafish (Souza et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%